THE ART OF DIRECTING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
An analysis of the role of a play in the art of filmmaking (profession) is one of the most important factors in the hierarchy of the filmmaker. Because thorough analysis of the play, the discovery of content, the ability to create an environment that matches the genre of the stage work through various noises, the invention of its shape, and the careful composition of the stage work are the basis.